Impact Of Warehouse Receipt System On Access To Markets And Income Of Smallholder Maize Farmers In The Northern Region Of Ghana - Safo, N.K. (University of Ghana, 2017)
Smallholder farmers have limited access to credit for their farming activities due to lack of collaterals that are acceptable by formal financial institutions. The farmers sell immediately after harvest at low prices to ease their financial constraints, which consequently earn them low incomes. In order to overcome these problems, warehouse receipt system (WRS) is suggested as the best alternative scheme. The WRS in Africa however lacks legal and institutional framework to ensure its successful operation. The system is mostly used by large processors, importers and exporters to secure loans for their transactions, and it is unavailable to smallholder farmers who suffer most from financial exclusion due to lack of collateral. This thesis therefore assesses the impact of WRS on access to markets and income of smallholder maize farmers in the Northern Region of Ghana. The study specifically sought to address the following issues: the institutional arrangements of WRS in Ghana, extent of farmers’ awareness and perception of WRS, and effect of WRS on access to credit, output market and farm income. Data was collected from 400 randomly selected maize farmers in six communities in the Northern Region. Apart from descriptive statistics, endogenous switching regression model (ESRM) and propensity score matching (PSM) were employed to assess the effect of WRS on access to credit, output market, and crop income. In terms of institutional arrangements, the study identified partial legislation and slow implementation of commodity exchange market as the key limitations to successful operation of WRS. Over 80% of the farmers perceived the improved storage, market access and reduced transportation cost as the three most important benefits of WRS. The three most important WRS constraints perceived by the majority (80%) of farmers were: unfavourable condition of community warehouses, lack of insurance at community warehouses, and a few lending institutions supporting the system. About 35% of farmers participated in the WRS in 2016. Findings from both the ESRM and the PSM show that the main factors that positively affect smallholder farmers’ participation in WRS are education, farm size, level of production of maize, and membership of farmer-based organisation. Ownership of storage facility, cost of inputs, and payment of taxes reduce the possibility of participation in WRS. Participating in WRS has the potential to increase 1) amount of credit accessed by GH¢219.82 per annum, 2) quantity of maize supplied by 18%; and crop income of smallholder farmers by 13%. In order to sustain the positive impact of WRS, farmers should be encouraged to expand their farm sizes and join FBOs for consistent learning. Policy makers should facilitate the passage of “commodity exchange and warehouse receipt system bill” into law. The law and an active commodity exchange market will boost the confidence of financial institutions to support the WRS.
Thesis (PhD)
Keywords: Warehouse Receipt System; Access To Markets; Income; Smallholder Maize Farmers; Northern Region; Ghana